1990
DOI: 10.1113/jphysiol.1990.sp018208
|View full text |Cite
|
Sign up to set email alerts
|

Reflex coronary vasodilation evoked by chemical stimulation of cardiac afferent vagal C fibres in dogs.

Abstract: SUMMARY1. Veratridine injected into the coronary circulation stimulates afferent vagal endings in the heart to evoke bradycardia and systemic hypotension (Bezold-Jarisch reflex, coronary chemoreflex) and coronary vasodilatation. We have examined certain features of the reflex coronary vasodilator response in anaesthetized dogs.2. When the circumflex coronary artery was perfused at constant pressure (100 mmHg), injection of veratridine (03 Ig kg-1) into the anterior descending artery decreased blood pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
13
1
1
Order By: Relevance
“…Although data from Duncker et al indicate that the withdrawal of parasympathetic activity may facilitate β-adrenoceptor dilation in swine during exercise (280), the effects of the parasympathetic nervous system on the control of coronary blood flow are quite modest under most physiologic conditions (198, 280, 332, 335). However, there is evidence to support a role for parasympathetic coronary vasodilation in the carotid chemoreceptor reflex (430,442,700,703,950), Bezold-Jarisch reflex (186,330,1027), and during activation of afferent vagal C fibers in the lung (187, 734). …”
Section: Neural Controlmentioning
confidence: 99%
“…Although data from Duncker et al indicate that the withdrawal of parasympathetic activity may facilitate β-adrenoceptor dilation in swine during exercise (280), the effects of the parasympathetic nervous system on the control of coronary blood flow are quite modest under most physiologic conditions (198, 280, 332, 335). However, there is evidence to support a role for parasympathetic coronary vasodilation in the carotid chemoreceptor reflex (430,442,700,703,950), Bezold-Jarisch reflex (186,330,1027), and during activation of afferent vagal C fibers in the lung (187, 734). …”
Section: Neural Controlmentioning
confidence: 99%
“…Injection of the chemical agents caused a reflex increase in coronary blood flow and myocardial blood flow to all layers of the ventricular wall, and involved afferent non-myelinated vagal fibres. In contrast to the findings of Zucker et al (1987), the efferent pathways were shown by the use of atropine and phentolamine to involve both vagal and sympathetic effects (Clozel et al 1990). The differences between the two reports may be attributed to a greater efferent sympathetic activity in anaesthetized animals since the response entailed withdrawal of this activity.…”
Section: Ventricular Receptorsmentioning
confidence: 81%
“…More recently, this reflex was re-examined in anaesthetized dogs in which veratridine or capsaicin was injected into the left anterior descending artery (Clozel, Pisarri, Coleridge & Coleridge, 1990). Responses of blood flow were measured by an electromagnetic flowmeter probe in the left circumflex coronary artery which was perfused by arterial blood at constant pressure through a cannula wedged into this coronary artery.…”
Section: Ventricular Receptorsmentioning
confidence: 99%
“…Carley and coworkers further demonstrated that two other pharmacologic activators of vagal afferents, capsaicin (Hedner et al 1985) and protoveratrine (Clozel et al 1990) also increased spontaneous SRBD in rats (Trbovic et al 1997; Carley et al 2004). Interestingly, unlike serotonin, capsaicin, which activates primarily c-fibers, and protoveratrine, which stimulates free nerve endings, increased apnea expression only during NREM sleep (Figs.…”
Section: Vagus Nerve Apneic Reflexesmentioning
confidence: 99%